2000
DOI: 10.1128/aac.44.3.693-696.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind Placebo-Controlled Study of an Infusion of Lexipafant (Platelet-Activating Factor Receptor Antagonist) in Patients with Severe Sepsis

Abstract: Platelet-activating factor (PAF) is a potent endogenous proinflammatory mediator implicated in the pathogenesis of septic shock. A double-blind randomized placebo-controlled trial of an intravenous PAF receptor antagonist (lexipafant) was conducted with 131 adult Thai patients with suspected severe sepsis (66 of whom had positive blood cultures). Detailed serial clinical, biochemical, and cytokine measurements were performed. Lexipafant treatment was well tolerated. The 28-day mortality in the lexipafant group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…This tenet is further reinforced by the studies showing that serum levels of PAF acetylhydrolase, which inactivates PAF, are decreased in severe sepsis (61,62) and that PAFR antagonists improve resistance against the lethal effects of experimental endotoxemia (16 -20). However, clinical trials with recombinant human PAF acetylhydrolase or PAFR antagonists have not been shown to reduce the mortality of patients with severe sepsis (21)(22)(23). Similarly, we observed that the protective effect of PAFR antagonist reduced when it was used as posttreatment protocol (Fig.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This tenet is further reinforced by the studies showing that serum levels of PAF acetylhydrolase, which inactivates PAF, are decreased in severe sepsis (61,62) and that PAFR antagonists improve resistance against the lethal effects of experimental endotoxemia (16 -20). However, clinical trials with recombinant human PAF acetylhydrolase or PAFR antagonists have not been shown to reduce the mortality of patients with severe sepsis (21)(22)(23). Similarly, we observed that the protective effect of PAFR antagonist reduced when it was used as posttreatment protocol (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, the overexpression of the PAFR increases lethality in response to LPS administration in mice (14), and the administration of PAFR antagonists to animals and humans protect them from the deleterious effects of LPS (15)(16)(17)(18)(19)(20). However, clinical trials using recombinant human PAF acetylhydrolase or PAFR antagonists failed to reduce the mortality of severe septic patients, although a substantial reduction in organ dysfunction was achieved (21)(22)(23).…”
mentioning
confidence: 99%
“…In a randomized placebo-controlled trial in Thailand involving 131 patients, no significant difference in mortality was observed in patients with severe sepsis, including 36 patients with melioidosis (418). Although exogenous administration of G-CSF has not been associated with improved outcomes in patients with pneumonia and/or severe sepsis in large clinical trials (310,311,361), melioidosis may differ from infections due to other organisms because of the key role of neutrophils in patients with recognized risk factors for neutrophil defects.…”
Section: Management Of Sepsis Syndromementioning
confidence: 99%
“…In subsequent studies, increased PAF bioactivity was also reported in plasma samples from patients with bacteremia compared with blood from control subjects (Heuer 1991). Despite encouraging results with PAF receptor antagonists in animal models of endotoxemia and sepsis (Chang et al 1987, Rabinovici et al 1990), most of the clinical trials conducted with these drugs have not confirmed the benefits of these drugs in humans (Dhainaut et al 1998, Suputtamongkol et al 2000. Importantly, Graham et al (1994) reported decreased PAF-AH plasma activity in blood samples from septic patients and that the half-life of PAF was prolonged in the plasma of septic patients who died compared to survivors or normal volunteers.…”
Section: Paf-ah In Diseases and Disease Modelsmentioning
confidence: 99%